Perbankan Syariah sebagai Manifestasi Gerakan Ekonomi di Indonesia - Iwan Wisandani (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2007)
In Indonesia, Islamic (Shariah) banking discourse came up in 80's decade, followedby other Islamic finance institutions in 90's and 2000's. Most of them are still oriented to the finance sector and only a few of them which pay attention to the real sector. In fact those two factors could be tied together to face the future.